2010
DOI: 10.2174/156802610791268756
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptors: What We Know and What We are Learning

Abstract: Adenosine, beside its role in the intermediate metabolism, mediates its physiological functions by interacting with four receptor subtypes named A(1), A(2A), A(2B) and A(3). All these receptors belong to the superfamily of G protein-coupled receptors that represent the most widely targeted pharmacological protein class. Since adenosine receptors are widespread throughout the body, they are involved in a variety of physiological processes and pathology including neurological, cardiovascular, inflammatory diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 215 publications
(308 reference statements)
0
37
0
Order By: Relevance
“…These broad-ranging actions of adenosine are mediated by A 1 , A 2A , A 2B , and A 3 adenosine receptors (24,45,86), and all four adenosine receptor subtypes are members of the 7-transmembrane spanning superfamily of G protein-coupled receptors.…”
Section: Discussionmentioning
confidence: 99%
“…These broad-ranging actions of adenosine are mediated by A 1 , A 2A , A 2B , and A 3 adenosine receptors (24,45,86), and all four adenosine receptor subtypes are members of the 7-transmembrane spanning superfamily of G protein-coupled receptors.…”
Section: Discussionmentioning
confidence: 99%
“…It plays important roles in cardiovascular, neurological, and renal diseases (5). In addition, adenosine functions as a potent pro-inflammatory mediator and contributes to the pathogenesis of inflammatory lung diseases, such as asthma and chronic obstructive pulmonary disease (6).…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate levels are also found in other brain regions, skeletal muscle, liver, kidney, adipose tissue, salivary glands, esophagus, colon, antrum and testis. Lung and pancreas present low levels of the A 1 ARs (Trincavelli et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Both the third intracellular loop and the C-terminal tail of A 1 AR are involved in G ia coupling. It has been reported that under certain conditions, the A 1 AR couples via G s to adenylyl cyclase stimulation or to G q/11 to stimulate inositol phosphate production (Trincavelli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%